Numerical Simulation of Methane Production from Hydrates Induced by Different Depressurizing Approaches - Xuke Ruan; Yongchen Song; Jiafei Zhao; Haifeng Liang; Mingjun Yang; Yanghui Li (Energies, 2012)
Several studies have demonstrated that methane production from hydrate-bearing porous media by means of depressurization-induced dissociation can be a promising technique. In this study, a 2D axisymmetric model for simulating the gas production from hydrates by depressurization is developed to investigate the gas production behavior with different depressurizing approaches. The simulation results showed that the depressurization process with depressurizing range has significant influence on the final gas production. On the contrary, the depressurizing rate only affects the production lifetime. More amount of cumulative gas can be produced with a larger depressurization range or lowering the depressurizing rate for a certain depressurizing range. Through the comparison of the combined depressurization modes, the Class 2 (all the hydrate dissociation simulations are performed by reducing the initial system pressure with the same depressurizing range initially, then to continue the depressurization process conducted by different depressurizing rates and complete when the system pressure decreases to the atmospheric pressure) is much superior to the Class 1 (different depressurizing ranges are adopted in the initial period of the gas production process, when the pressure is reduced to the corresponding value of depressurization process at the different depressurizing range, the simulations are conducted at a certain depressurizing rate until the pressure reaches the atmospheric pressure) for a long and stable gas production process. The parameter analysis indicated that the gas production performance decreases and the period of stable production increases with the initial pressure for the case of depressurizing range. Additionally, for the case of depressurizing range, the better gas production performance is associated with higher ambient temperature for production process, and the effect of thermal conductivity on gas production performance can be negligible. However, for the case of depressurizing rate, the ...